Investigating the microbial pathogens of sexually transmitted infections among heterosexual Vietnamese men with symptomatic urethritis. (31st December 2022) - Nguyen, Bac Hoai; Pham, Quan Minh; Hoang, Long; Sansone, Andrea; Jannini, Emmanuele A.; Tran, Chau Minh
Abstract: Objective: To explore the microbial etiology of urethritis in Vietnamese men and the association with patients' characteristics, especially their sexual behaviors. Methods: This study was conducted on 349 men who presented with symptomatic urethritis and evidence of STIs (determined by multiplex PCR tests) at the Department of Andrology and Sexual Medicine—Hanoi Medical University Hospital. All information regarding medical history, sexual activities, and symptoms of urethritis was documented. Results: C. trachomatis and N. gonorrhoea remained the two most common causative pathogens, followed by an unexpectedly high prevalence of Mycoplasma and Ureaplasma species. Coinfection was significant with a rate of 40.7%. Men who had sex with female sex workers (FSWs) were more likely to be positive with N. gonorrhoea but less likely to be positive with C. trachomatis and M. genitalium than those having sex with only one romantic partner. Conclusions: Our findings suggested the important role of other microorganisms, especially M. genitalium, in the etiology of urethritis in men besides the previously well-known causes of STIs. Since the coinfection rate is quite high, targeted treatment with clear microbial evidence should be considered rather than empiric antimicrobial therapy.